Situational Leadership During the Covid-19 Pandemic - Muhammad Jamil; Lisa Lazwardi; Sufyarma Marsidin; Demina Demina (IAIN Batusangkar, 2021)
Principals are leaders in educational institutions who have an influence on the achievement of the school's vision and mission. The regional situation that continues to change due to the Covid-19 pandemic requires leadership who is able to read the opportunities and challenges when the crisis is not over. Leadership with a situational approach is one form of solution in implementing the ever-changing educational process. Situational approach models which include contingency leadership, three-dimensional leadership and situational leadership models, are the right choice to be implemented in high school. Because the condition of the area that changes easily from the green, yellow and red zones demands changes in the learning process. With situational leadership any problems and changes in regional conditions can be overcome.